1977
DOI: 10.1002/ajpa.1330460116
|View full text |Cite
|
Sign up to set email alerts
|

On the meaning of increased fluctuating dental asymmetry: A cross populational study

Abstract: Suarez reports a greater magnitude of fluctuating dental asymmetry for Neandertal sample when compared with a sample of modern Ohio whites. He postulates that this greater antimeric variance could be due to a greater degree of inbreeding in the Neandertal populations. In the present investigation, the magnitude of fluctuating dental asymmetry is evaluated for Eskimo and Pueblo populations. These populations were found to exhibit dental variance of equal magnitude to that of the Neandertal population. As these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 16 publications
1
49
0
1
Order By: Relevance
“…These works corroborated the hypothesis that fluctuating asymmetry is an appropriate indicator for estimating intra-and inter-population developmental stability (Gilligan et al 2000;Bailit et al 1970;Doyle and Johnson 1977;Hersh kovitz et al 1993;Livshits et al 1994;DeLeon 2007;Gawlikowska et al 2007aGawlikowska et al , b and Özener 2010aGawlikowska et al , b, 2011.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These works corroborated the hypothesis that fluctuating asymmetry is an appropriate indicator for estimating intra-and inter-population developmental stability (Gilligan et al 2000;Bailit et al 1970;Doyle and Johnson 1977;Hersh kovitz et al 1993;Livshits et al 1994;DeLeon 2007;Gawlikowska et al 2007aGawlikowska et al , b and Özener 2010aGawlikowska et al , b, 2011.…”
Section: Discussionsupporting
confidence: 67%
“…FA analysis is useful in the examination of historic populations. For example, Doyle and Johnson (1977) studied fluctuating asymmetry of teeth in Eskimos from Alaska, American Indians from Arizona and current white males from Ohio and found the level lowest in modern white males. Perzigian (1977) studied differences in FA levels in three historic populations, with the highest levels noted in lowest socio-economic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence of low genetic variation in Neanderthals is consistent with this hypothesis [226,227]. Doyle and Johnson [228], however, compared dental asymmetry of Pueblo and Eskimo populations, in which inbreeding was not widespread, to that of Neanderthals. They found no significant differences between the groups and concluded that environmental stress is responsible for the observed asymmetry in Neanderthals, rather than inbreeding.…”
Section: Fossil Hominidsmentioning
confidence: 80%
“…focused on the influence of environmental factors on bilateral manifestation of these traits under a genetic background. Since the 1960s, it has been demonstrated, on the basis of a good number of morphological studies including those using laboratory animals, that environmental stresses are influential in bilaterality reduction (O'Connell, 1975;Doyle et al, 1977;Siegel et al, 1977;Trinkaus, 1978;Green et al, 1979;Perizonius, 1979;Livshits et al, 1988;Livshits and Kobyliansky, 1991). Therefore, the present findings appear to suggest that the effect of environmental factors is rather small in the formation of mylohyoid bridging.…”
Section: Populational Relationships Viewed From Mylohyoid Bridging Mementioning
confidence: 99%